The relationship between heavy metals and biomass properties in polymictic lake - Baharim, N.B.; Yusop, Z.; Yusoff, I.; Tahir, W.Z.W.M.; Askari, M.; Othman, Z.; Abidin, M.R.Z. (Penerbit Universiti Kebangsaan Malaysia, 2016)
The relationship between heavy metal and biomass properties in polymictic lake at Sembrong Lake, Peninsular Malaysia was assessed. Sixteen parameters, including heavy metals and biomass parameters were monitored. pH, temperature, dissolved oxygen and heavy metals level changes significantly influenced by the dynamic of polymictic mixing pattern. The mean concentrations of heavy metals in the reservoir decreased in the following order: Fe > Mn > Zn > Cu > As > Pb. The result showed that this polymictic lake is being threatened by cultural eutrophication with TSI value range from 72.40 to 80.41 and classified as a hypereutrophic lake. The levels of heavy metal pollution in the reservoir range from slightly polluted to polluted. Factor analysis was performed to determine the relationship between heavy metals and biomass parameters. Five factors were responsible for data structure and explained the 83% of total variance. These factors differentiate each group of parameters according to their common characteristics. Photosynthesis, respiration and redox processes were main factors contributing to the variability of both properties.